The Case for Increased Physical Activity in Chronic Inflammatory Bowel Disease: A Brief Review - Shephard, R. J. (International Journal of Sports Medicine, 2016)
Regular physical activity reduces the risk of colon cancer, but there is little information on the merits of such activity in the prevention and management of chronic inflammatory bowel disease (CIBD). The present systematic review thus documents current levels of habitual physical activity and aerobic and muscular function in CIBD, and examines the safety, practicality and efficacy of exercise programmes in countering the disease process, correcting functional deficits and enhancing quality of life. A systematic search of the Ovid/Medline database from January 1996 to May 2015 linked the terms physical activity/motor activity/physical fitness/physical training/physical education/training/exercise/exercise therapy with Crohn’s disease/colitis/ulcerative colitis/inflammatory bowel disease, supplementing this information by a scanning of reference lists and personal files.12 of 16 published studies show a low level of habitual physical activity in CIBD, with sub-normal values for aerobic power, lean tissue mass and muscular strength. 3 of 4 studies suggest physical activity may reduce the risk of developing IBD, and 11 interventions all note that exercise programmes are well tolerated with some decreases of disease activity, and functional gains leading to an increased health-related quality of life. Moreover, programme compliance rates compare favourably with those seen in the treatment of other chronic conditions. More information on mechanisms is needed, but regular moderate aerobic and/or resistance exercise improves the health status of patients with CIBD both by modulating immune function and by improving physical function. A regular exercise programme should thus become an important component in the management of CIBD.
Keywords: crohn’s disease; habitual physical activity; immunoregulation; lean tissue mass; maximal aerobic power; quality of life; strength; ulcerative colitis